Molecular signature incorporating the immune microenvironment enhances thyroid cancer outcome prediction - George J. Xu; Matthew A. Loberg; Jean-Nicolas Gallant; Quanhu Sheng; Sheau-Chiann Chen; Brian D. Lehmann; Sophia M. Shaddy; Megan L. Tigue; Courtney J. Phifer; Li Wang; Mario W. Saab-Chalhoub; Lauren M. Dehan; et al. (Elsevier, 2023)
Summary: Genomic and transcriptomic analysis has furthered our understanding of many tumors. Yet, thyroid cancer management is largely guided by staging and histology, with few molecular prognostic and treatment biomarkers. Here, we utilize a large cohort of 251 patients with 312 samples from two tertiary medical centers and perform DNA/RNA sequencing, spatial transcriptomics, and multiplex immunofluorescence to identify biomarkers of aggressive thyroid malignancy. We identify high-risk mutations and discover a unique molecular signature of aggressive disease, the Molecular Aggression and Prediction (MAP) score, which provides improved prognostication over high-risk mutations alone. The MAP score is enriched for genes involved in epithelial de-differentiation, cellular division, and the tumor microenvironment. The MAP score also identifies aggressive tumors with lymphocyte-rich stroma that may benefit from immunotherapy. Future clinical profiling of the stromal microenvironment of thyroid cancer could improve prognostication, inform immunotherapy, and support development of novel therapeutics for thyroid cancer and other stroma-rich tumors.